Pengaruh Citra Merek Dan Electronic Word Of Mouth Terhadap Minat Beli Produk Kecantikan Wardah - Novia Roudhlotul Janah; Edi Suswardji (COSTING : Journal of Economic, Business and Accounting, 2021)
This research aims to find out how big the brand image and Electronic Word Of Mouth affect the buying interest in Wardah beauty products. The study used a descriptive and vernacular approach to sampling techniques using Nonprobability Sampling with respondents amounting to 135. Data were analyzed using path analysis with SPSS version 26. The result of the relationship between brand image and electronic word of mouth has a correlation coefficient of 0.498 and has a medium and direct relationship level due to positive values, the partial effect of brand image on buying interest is 24.7%, indicating that brand image has a positive influence with buying interest, the partial effect of electronic word of mouth on buying interest is 18.2%. It shows that electronic word of mouth on buying interest has a positive effect, the simultaneous effect of brand image and electronic word of mouth on buying interest amounted to 43.1%. This shows that the variable brand image and electronic word of mouth have a strong enough influence on buying interest Wardah beauty products. But there are still other variable factors not examined around 56.9% Keywords : Brand Image, Electronic Word of Mouth, Buying Interest.